2009
DOI: 10.1007/s00464-008-0277-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of laparoscopic Nissen fundoplication as a day-case procedure

Abstract: LNF in day-care is feasible and safe, but postoperative pain scores are high and most prefer short hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…There were no randomized trials or meta-analyses included in the study. The studies identified were one prospective comparative study (comparing 22 outpatient surgeries to 16 inpatient surgeries, level 3b) [8], nine prospective noncomparative studies (level 4) [5,[9][10][11][12][13][14][15][16], and four retrospective noncomparative studies (level 4) [17][18][19][20] of which one involved children [20] and was analyzed separately. A literature review without data metaanalysis was published in 2005 and involved only seven published studies [21].…”
Section: Publications Identifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no randomized trials or meta-analyses included in the study. The studies identified were one prospective comparative study (comparing 22 outpatient surgeries to 16 inpatient surgeries, level 3b) [8], nine prospective noncomparative studies (level 4) [5,[9][10][11][12][13][14][15][16], and four retrospective noncomparative studies (level 4) [17][18][19][20] of which one involved children [20] and was analyzed separately. A literature review without data metaanalysis was published in 2005 and involved only seven published studies [21].…”
Section: Publications Identifiedmentioning
confidence: 99%
“…All study results are presented in Table 1. Ten publications dealing with day-case surgery (hospital stay \12 h, mainly coming from Europe) were identified (8 prospective [9][10][11][12][13][14][15][16], 2 retrospective [17,18]), each of them enrolling between 20 and 310 adult patients for a total of 876 adult patients. Three publications dealing with outpatient surgery (hospital stay \24 h, mainly coming from the US) were identified (2 prospective [5,8], 1 retrospective [19]), each of them enrolling between 4 and 557 adult patients for a total of 583 adult patients.…”
Section: Number Of Patients Enrolledmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) is an important indicator of the principal outcome for laparoscopic cholecystectomy (LC) [1,2]. Studies indicate that LC surgery substantially improves HRQoL [3,4].…”
mentioning
confidence: 99%
“…Despite their contributions, previous studies of the longterm outcomes for LC have had significant shortcomings [1][2][3][7][8][9]. First, few used longitudinal data with more than two time points.…”
mentioning
confidence: 99%
See 1 more Smart Citation